The ghosts of collections past: characterisation of Neohouzeaua mekongensis (Poaceae: Bambusoideae: Bambuseae: Melocanninae) with an epitype - Sungkaew, Sarawood; Teerawatananon, Atchara; Goh, Wei Lim; Rattamanee, Chakkrapong; Ohrnberger, Dieter; Xia, Nianhe; Wong, Khoon Meng (Thai Forest Bulletin (Botany), 2021)
Identifying a bamboo taxon from the Asian seasonal tropics is notoriously difficult, if not impossible, especially when the type material is lacking vegetative parts. This is due to the fact that old type material associated with the naming of bamboos often consists of only flowering branches and perhaps just a few leaves, and, as bamboos in the field are vegetative for prolonged periods prior to flowering, they are therefore not easily identifiable much of the time. Investigating one such bamboo, Neohouzeaua mekongensis, we show that previous flowering collections made during the seasonal dry (flowering) season could not have easily included key vegetative parts, such as the culm sheaths, which would have assisted in their recognition at other times. We trace this species back to its type localities and propose an epitype in order that its vegetative characteristics are made available to complement the floral characteristics of the original material.